Selection of window for inter-pulse analysis of simple pulsed radar signal using the short time Fourier transform - Ahmad, Ashraf Adamu; Daniyan, Abdullahi; Gabriel, David Ocholi (International Journal of Engineering and Technology, 2015)
The electronic intelligence (ELINT) system is used by the military to detect, extract information and classify incoming radar signals. This work utilizes short time Fourier transform (STFT) - time frequency distribution (TFD) for inter-pulse analysis of the radar signal in order to estimate basic radar signal time parameters (pulse width and pulse repetition period). Four well-known windows functions of different and unique characteristics were used for the localization of STFT to determine their various effects on the analysis. The window functions are Hamming, Hanning, Bartlett and Blackman window functions. Monte Carlo simulation is carried out to determine the performance of the signal analysis in presence of additive white Gaussian noise (AWGN). Results show that the lower the transition of main lobe width and higher the peak side lobe, the better the performance of the window function irrespective of time parameter being estimated. This is because 100 percent probability of correct estimation is achieved at signal to noise ratio of about -2dB for Bartlett, 4dB for both Hamming and Hanning, and 9dB for Blackman.
Keywords: Additive White Gaussian Noise (AWGN); Airborne Radar; Electronic Warfare; Signal Analysis; Signal to Noise Ratio.